Gender and promoting quality seeds in Africa: A literature review - Brearley, Emily; Kramer, Berber (ISSD Africa, 2020)
Advances in plant breeding and biotechnology have the potential to transform agriculture in Africa, but sustainable and inclusive distribution and marketing of quality seeds remains a significant challenge. We review the peer-reviewed literature on alternative approaches for promoting improved varieties and quality seeds in Africa, focusing on how adoption and use can be enhanced for women and men alike. The analysis explores a range of innovations that have been developed in recent years with the aim to boost the availability and quality, access to and, control and use of seeds. The literature review highlights pockets of innovative models on both the public and private sector side. However, many of these approaches are not tested with a gender lens. In fact, many innovations risk increasing productivity for a small segment of the farming population, thereby potentially further widening the large gender gaps in empowerment in agriculture. Given the current understanding of intrahousehold gender dynamics and contextual crop-specific constraints across the value chain, there is an urgent need to start testing, measuring and documenting both the sustainability and inclusiveness of alternative innovations to promote the use of high-quality seeds.